Sensitivity Analysis of Workspace Conflicts According to Changing Geometric Conditions - Rohani, M.; Shafabakhsh, G.; Haddad, A.; Asnaashari, E. (Engineering, Technology & Applied Science Research, 2017)
Workspace conflicts and building components can happen in different forms and both permanently and temporarily. These spatial clashes affect the work process and deplete the project process. Geometric clash detection system of 4D simulation tools can identify the number of clashes for construction resources in the worksite to improve workflow planning. In the present research, building components and their corresponding workspaces were simulated, based on the schedule and activities, using a visual simulation tool. First, the total daily volumes of workspace were calculated according to the activities' schedule and compared by the available space in order to determine the critical days for the project. Then, the number of time-based conflicts were examined and analyzed for building components and resources among activities and by different tolerance distances. The main objective of this study was to evaluate the sensitivity analysis of clash numbers based on the geometrical conditions in different statuses (Inflexible, Semi-flexible and flexible) to assist the planner for detecting real conflicts. The results show that the tolerance distance of 0.2 to 1 meter for the clashes of workspace and the building components and 0.2 to 2 meters for the clashes of workspaces with each other to provide realistic results of actual construction operation conflicts. By the help of this methodology, the project planners are able to identify and prioritize the effective conflicts on the work process in comparison to the clashes resulted from iteration or minor design inaccuracy.